Dynamic Analysis of Construction and Demolition Waste Management System (A Case Study of Tehran, Iran) - Milad Ghanbari (Advances in Civil Engineering)
Increasing construction and demolition (C&D) waste generation has faced serious challenges in the metropolitan areas of Iran. The objective of this research is to present a system dynamics model for C&D waste management of Tehran. In particular, variables such as energy consumption and carbon dioxide (CO2) emissions for the city of Tehran to the horizon of 2041 are studied and predicted. Increasing the rate of construction of housing and urban infrastructure will increase C&D waste and, on the other hand, increase the demand for raw materials, which is contrary to the principles of sustainable development. The increase in quarries exploitation and the increase in C&D waste generation can reduce the buildable area of the city. The impacts of such factors are in a cyclic and systemic approach that either reinforces a destructive factor or balances the existing solution. In general, the assessment of the implementation or nonimplementation of C&D waste recycling in each city requires a system insight that examines the aspects of the subject with a systemic perspective over time. To this end, the system dynamic approach, along with the environmental and economic approach of the life cycle, can clarify the hidden dimensions of the problem. One of the important limitations of the research is the large number of variables in the model and finding reliable historical information for these variables.